Improving wave energy conversion performance of a floating BBDB-OWC system by using dual chambers and a novel enhancement plate - Chen, Wenchuang; Xie, Weixin; Zhang, Yongliang; Wang, Chen; Wang, Liguo; Huang, Luofeng (Elsevier, 2024)
In this study, a novel floating dual-chamber backward bent duct buoy oscillating water column (BBDB-OWC) wave energy converter (WEC) is introduced, featuring a horizontal plate at the bottom of the front chamber to act as an enhancement plate. A three-dimensional computational fluid dynamics (CFD) model is developed and validated by comparing its results with existing experimental measurements. The validated model is employed to investigate the hydrodynamic performance and power generation characteristics of the dual-chamber BBDB-OWC WEC under various conditions, including variations in the length of the horizontal plate (lp/lf) and different regular wave conditions. Key performance metrics, including peak to average ratio of power (PTARP), wave energy capture width ratio (ξtotal), and its wave period respond bandwidth (indicated by Pξtotal > 0.5 and Pξtotal > 0.7), are analyzed and compared with those of a traditional single-chamber BBDB-OWC WEC. The results reveal that, compared to the single-chamber WEC, the dual-chamber WEC with a specific horizontal plate length reduces the average PTARP from 2.88 to a minimum value of 1.82 for lp/lf = 0.5, improves the average ξtotal from 0.55 to a maximum value of 0.64 for lp/lf = 2.5, and increases Pξtotal > 0.5 and Pξtotal > 0.7 from 71 % and 14 % to maximum values of 86 % and 43 % for lp/lf = 2.5, respectively. An explanation for these observations is also provided in the context of structure motion and flow fields.
Keywords: Wave energy; Backward bent duct buoy (BBDB); Dual-chamber; Enhancement plate; Peak to average ratio of power; Capture width ratio